MODEL OF MICROCLIMATIC INFLUENCE ON FLUCTUATION OF HERPETOFAUNA DIVERSITY IN CAMPUS AREA - Tony F. Qurniawan (Universitas Gadjah Mada, 2015)
The study on correlation of microclimates changes on fluctuations of herpetofauna diversity in campus area wasdone for the last six years. Monitoring herpetofauna diversity was conducted from 2007 to 2012 using VisualEncounter Survey. The analysis for designing a model on the influence of microclimates on fluctuations ofherpetofauna diversity performed by using smart PLS program. The result showed eight (8) species of amphibiansand twenty four (24) species of reptiles were identified within the last six-year visits (2007-2012). New country recordsof Lepidodactylus cf lugubris (Geckonidae) species were documented. The results also showed that fluctuations ofherpetofauna diversity in campus area was influenced by microclimates elements. The model of microclimaticinfluence on fluctuations of herpetofauna diversity showed that the humadity becomes a major factor influencingon fluctuations of herpetofauna diversity in campus area with the predictive-relevance (Q2) value is 99,817%.